Ecosystem services may provide large economic values in Kenya and Vietnam: A value transfer application based on results from a systematic literature review - Hettiarachchi, Upeksha; Zhang, Wei; Pham, Thuy Thu; Davis, Kristin E.; Fadda, Carlo (International Food Policy Research Institute, 2023)
This study focuses on the valuation of ecosystem services in Kenya and Vietnam, two countries that have received much attention from the international development community for their biodiversity significance, opportunities for scaling, climate and poverty challenges, and political will. Using The Economics of Ecosystems and Biodiversity (TEEB) framework and the Millenium Ecosystem Assessment (MEA), this study estimates per hectare values of ecosystem services in Kenya and Vietnam based on a systematic literature review of studies on the values of ecosystem services in both countries. Provisioning services, such as medicines, timber, and non-timber forest products were better studied than regulating, supporting and cultural ecosystem services, underscoring the need for further research to better estimate the values of non-tangible services which would improve the estimation of total value of ecosystem services in Kenya and Vietnam. To complement the national level analysis, we selected forest biomes to conduct a value transfer analysis. Forests provide ecosystem service benefits worth $25.78 billion for Kenya and $35.6 billion in Vietnam in 2022 USD. In comparison, the agricultural sector contributed $48.50 billion to Vietnam’s GDP and $24.10 billon to Kenya’s GDP in 2021. The per hectare values for ecosystem services are used in a value transfer analysis to estimate the total value of forest ecosystem services in Vietnam and Kenya. The average per hectare value of ecosystem services provided by forests in Kenya is $5,718.50 ha−1 yr−1 estimated within a range spanning $1,609.44 to $15,606.62 ha−1 yr−1 , while Vietnam's forests demonstrate an average value of $3,650.20 ha−1 yr−1 , with a range of $84.93 to $8,978.16 ha−1 yr−1 . We project the loss of forests into 2050 and estimate the annual economic loss of ecosystem services at $48.08 million for Kenya and $76.29 million for Vietnam, respectively, if deforestation and forest degradation continue at the current rates. Our approach presents a comprehensive overview of diverse ecosystem services, equipping policymakers with a nuanced comprehension of ecosystems’ inherent value. By consolidating values from the literature into a national-level estimate, we provide compelling evidence at a broader scale for informed decision-making. Despite the well-known limitations of value transfer method and with caveats, the values presented in our paper can provide a guiding reference for incorporating these estimations into broader policymaking endeavors.